Development of a self-report questionnaire designed for population-based surveillance of gingivitis in adolescents: assessment of content validity and reliability - Viviana QUIROZ; Daniela REINERO; Patricia HERNÁNDEZ; Johanna CONTRERAS; Rolando VERNAL; Paola CARVAJAL
Abstract The major infectious diseases in Chile encompass the periodontal diseases, with a combined prevalence that rises up to 90% of the population. Thus, the population-based surveillance of periodontal diseases plays a central role for assessing their prevalence and for planning, implementing, and evaluating preventive and control programs. Self-report questionnaires have been proposed for the surveillance of periodontal diseases in adult populations world-wide. Objective This study aimed to develop and assess the content validity and reliability of a cognitively adapted self-report questionnaire designed for surveillance of gingivitis in adolescents. Material and Methods Ten predetermined self-report questions evaluating early signs and symptoms of gingivitis were preliminary assessed by a panel of clinical experts. Eight questions were selected and cognitively tested in 20 adolescents aged 12 to 18 years from Santiago de Chile. The questionnaire was then conducted and answered by 178 Chilean adolescents. Internal consistency was measured using the Cronbach's alpha and temporal stability was calculated using the Kappa-index. Results A reliable final self-report questionnaire consisting of 5 questions was obtained, with a total Cronbach's alpha of 0.73 and a Kappa-index ranging from 0.41 to 0.77 between the different questions. Conclusions The proposed questionnaire is reliable, with an acceptable internal consistency and a temporal stability from moderate to substantial, and it is promising for estimating the prevalence of gingivitis in adolescents.